2015
DOI: 10.1111/tmi.12560
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Ugandan health services for the management of outpatients with chronic diseases

Abstract: ObjectiveTraditionally, health systems in sub‐Saharan Africa have focused on acute conditions. Few data exist on the readiness of African health facilities (HFs) to address the growing burden of chronic diseases (CDs), specifically chronic, non‐communicable diseases (NCDs).MethodsA stratified random sample of 28 urban and rural Ugandan HFs was surveyed to document the burden of selected CDs by analysing the service statistics, service availability and service readiness using a modified WHO Service Availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
131
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(148 citation statements)
references
References 17 publications
15
131
0
2
Order By: Relevance
“…Most of our results come from a single hospital. This hospital, though, is similar to other government hospitals in East Africa, 10,11 and our results at a second public hospital in Tanzania confirm similar mortality rates. In addition, our study design should be relatively simple to replicate since our study demonstrated that 99% of hospitalized adults had access to mobile phones, and we successfully contacted >90% of participants (or their proxies) 12 months after discharge.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Most of our results come from a single hospital. This hospital, though, is similar to other government hospitals in East Africa, 10,11 and our results at a second public hospital in Tanzania confirm similar mortality rates. In addition, our study design should be relatively simple to replicate since our study demonstrated that 99% of hospitalized adults had access to mobile phones, and we successfully contacted >90% of participants (or their proxies) 12 months after discharge.…”
Section: Discussionsupporting
confidence: 85%
“…The resources of BMC are similar to those available in other government hospitals in East Africa. 10,11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,18 The delay in diagnosis in HF until the time of the index hospital admission is likely related to the limitations in resources for diagnoses of HF at lower level health facilities. 7,8 Therefore, as supported by evidence from the U.S., 19,20 we have identified the post-hospital period as a critical window of interventional opportunity for improving HF outcomes in Africa.…”
Section: Discussionmentioning
confidence: 67%
“…5 At our own hospital, HF represents 10% of hospital admissions and 10% of in-hospital deaths. 6 In addition, primary healthcare resources for managing chronic diseases such as HF are severely limited in sub-Saharan Africa, 7,8 with most service provided at hospitals instead of community health facilities.…”
Section: Introductionmentioning
confidence: 99%